"Everyone has the right to their opinion": "Gender Ideology" Rhetoric and Epistemic Struggles in Slovak Policymaking. (5th May 2021) - Valkovičová, Veronika; Meier, Petra
Abstract: Through the case study of the Slovak Committee on Gender Equality, a governmental advisory body, this article draws upon the growing literature on "gender ideology" rhetoric in Central and Eastern Europe to study the efforts of advocates of that rhetoric to gain access to policymaking structures. With the aid of narrative research, we examine the Committee's struggles over appropriate terminology and discourse, data and research, and ultimately the status of experts. This shows how "gender ideology" rhetoric serves to delegitimize gender knowledge, and how it eventually turns into knowledge itself.